Investigating the effect of nativeness and speaker age on the credibility of spoken sentences - Truong, Thanh Lan; Weber, Andrea (Frontiers in Language Sciences, 2024)
Previous studies found mixed results regarding a bias in credibility ratings for trivia statements made by L2 speakers in comparison to L1 speakers. Perceptual fluency, social attitudes, and pragmatic lenience have been proposed as underlying causes for the bias. The present study examined credibility ratings for L2 speakers and extended the scope of the investigation by adding the factor age of the speaker. In the present study, German native adult listeners were asked to judge the credibility of trivia statements recorded by L2 adults and L1 children in Experiment 1 and statements by L1 adults and L1 children in Experiment 2. In Experiment 1, the ratings showed no difference in credibility between the L2 adult statements and the L1 child statements. In Experiment 2, listeners rated statements from L1 child speakers as more credible than statements from L1 adult speakers, suggesting a positive bias for the credibility of children. The results are discussed in terms of their relevance for previously suggested causes contributing to a credibility bias.